PGC1β Regulates Breast Tumor Growth and Metastasis by SREBP1-Mediated HKDC1 Expression - Chen, Xiaoli; Lv, Yang; Sun, Ying; Zhang, Hongyu; Xie, Weiguo; Zhong, Liyan; Chen, Qi; Li, Min; Li, Ling; Feng, Jia; Yao, Athena; Zhang, Qi; et al. (Frontiers in Oncology, 2019)
Background. Breast cancer is a very common cancer with significant premature mortality in women. In this study, we show that HKDC1 expression in breast cancer cells is increased significantly. We aim to investigate the detailed mechanism for the regulation of HKDC1 expression and its potential contribution to tumorigenesis. Methods. Gene expression was evaluated by real time PCR, western blotting and immunohistochemistry. The mechanism for PGC1β/SREBP1-mediated HKDC1 expression was investigated using luciferase reporter assay, chromatin immunoprecipitation, and siRNA techniques. In addition, HKDC1 was overexpressed or knocked down by lentivirus to evaluate the potential effect on in vitro cell proliferation, glucose uptake, mitochondrial function, apoptosis and reactive oxygen species (ROS) formation. Furthermore, an in vivo xenograft tumor development study was employed to investigate the effect of HKDC1 on tumor growth and mouse survival. Results. HKDC1 is highly expressed in both breast cancer cells and clinical tumor tissues. HKDC1 expression is upregulated and coactivated by PGC1β through SREBP1 binding motif on the HKDC1 promoter. HKDC1 is located on the mitochondrial membrane and regulates the permeability transition pore opening by binding with VDAC1, subsequently modulating glucose uptake and cell proliferation. Overexpression of HKDC1 increases while knockdown of HKDC1 decreases in vitro breast cancer cell proliferation and in vivo tumor growth, metastasis and mouse survival. Conclusions. PGC1β regulates breast cancer tumor growth and metastasis by SREBP1-mediated HKDC1 expression. This provides a novel therapeutic strategy through targeting the PGC1β/HKDC1 signaling pathway for breast cancer treatment.